Urdu Ghazal and Dr Frances Pritchett - Arifa Shahzad (بازیافت, 2018)
As a student of Urdu, Frances Pritchett remembers her first experience of the ghazal, the preeminent genre of classical Urdu poetry...was love at first sight. But much to her puzzelment and dismay, she discovered that modern urdu critics generally approach the classical ghazal with appology, or even open disdain. In Nets of Awareness, Pritchett joins literary criticism and history to explain how ghazal,for centuries pride and joy of indo Muslim cilture,was abruptly dethroned devalued with in its own mileue by its own thoerists.This break with tradition was so sharp that today many aspects of the ghazal remain obsecure,and often distasteful to modern reader. The cause of this abrupt shift ,Pritchett argues ,was not literary at all,but political.Pritchett shows how British suppession of the Mutiny and subsequent rule had disastrous cultural as well as political consequences. In short, Pritchett shows us precisely the complexity and power of ghazal.